2017
DOI: 10.2134/agronj2017.02.0099
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Nutritive Value, and Preference of Annual Warm‐Season Grasses Grazed by Horses

Abstract: Core Ideas Teff, sudangrass, and sorghum sudangrass have potential as pasture forage for horses. Japanese and Siberian millet have little regrowth and are not ideal for pastures. Inverted Ca/P and high NO3–N were observed and should be determined prior to grazing. Annual warm‐season grasses have the potential to provide forage, but are rarely evaluated under horse (Equus caballus) grazing. The objectives were to determine yield, forage nutritive values, and preference of annual warm‐season grasses at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
14
2
Order By: Relevance
“…Previous research has reported distinct preferences for horses grazing different forage species (Allen et al., 2013; DeBoer et al., 2017; Grev et al., 2017); however, few studies have evaluated horse preference of binary mixtures. When horses grazed perennial cool‐season grasses in monoculture, Kentucky bluegrass and meadow fescue were among the most preferred grasses (>60% removal), whereas orchardgrass was among the least preferred (47% removal) (Allen et al., 2013).…”
Section: Horse Preferencementioning
confidence: 99%
“…Previous research has reported distinct preferences for horses grazing different forage species (Allen et al., 2013; DeBoer et al., 2017; Grev et al., 2017); however, few studies have evaluated horse preference of binary mixtures. When horses grazed perennial cool‐season grasses in monoculture, Kentucky bluegrass and meadow fescue were among the most preferred grasses (>60% removal), whereas orchardgrass was among the least preferred (47% removal) (Allen et al., 2013).…”
Section: Horse Preferencementioning
confidence: 99%
“…Weight management is often the focus of equine feeding programs, with 30% to 50% of horses classified as overweight ( Fernandes et al, 2015 ; Robin et al, 2015 ; Jaqueth et al, 2018 ). Additionally, due to lower non-structural carbohydrate (NSC) content, WSGs have been suggested as an alternative source of pasture forage for obese horses and horses with metabolic dysfunction where limiting dietary NSC is recommended ( Chatterton et al, 1989 ; Frank et al, 2010 ; DeBoer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, teff has been proposed for grazing dairy farms; however, very few farmers use teff in grazing pastures. Teff has lower yield than sorghum-sudangrass [ 16 , 17 ], but there is little information on how dairy cattle may perform and graze on teff. No research has compared brown-midrib sorghum × sudangrass (BMRSS) and teff by grazing dairy cattle.…”
Section: Introductionmentioning
confidence: 99%